Comparative analysis of flow dynamics studies between the straight and interrupted minichannel heat sink - Mat Tokit, Ernie; Yusoff, Mohd Zamri; Herawan, Safarudin Gazali (Penerbit Akademia Baru, 2025)
A simulation work was performed to investigate the advantage of interrupted minichannel heat sink over the straight one in terms of flow dynamics. Four different designs were examined, namely i) a straight, ii) Design A, iii) Design B and iv) Design C minichannel. All channels were rectangular in cross sectional area with 0.0032 m of hydraulic diameter, having cuts in between. Parametric studies were performed by utilizing the propylene glycol as the coolant fluid, while the Reynolds number are diverse between 510.9 to 608.2. The flow is modelled as steady and 3D flow. Comparative analysis between simulated and experimental data was first conducted as validation purposes with deviation of 0.49% to 9.81%, and 1.08% to 12.48% for Pdrop and Nusselt number respectively. The predicted results depicted the design features that affect the flow behaviours such as sharp corner edge that diminish Coanda effect and promotes flow separation, reverse flow and recirculation zone, and interrupts boundary layer. These behaviour causes the increment of heat flux and (Tout-Tin)/(Tw-Tm), while decrement in wall shear stress that finally augment the heat transfer. Comparative analysis showed that the increment in heat flux by 26.3% to 33.3%, (Tout-Tin)/(Tw-Tm) by 25% to 42.8%, and decrement in wall shear stress by 25% to 35.7%, indicating improved flow characteristics.